Nurses' consultative role to health promotion in patients with chronic diseases - Hojatollah Yousefi; Elaheh Sadat Ziaee; Parastoo Golshiri (Wolters Kluwer Medknow Publications, 2019)
AIMS: Although chronic diseases are the most common and expensive health problems, they are preventable too. Nurses play a key role in the care of these patients. One of the important roles of nurses is consultation role. Due to the high impact of nurse consultant role on health promotion and also the fact that this role is not fully understood in Iran, this study aims at clarifying the role of nurse consultant. MATERIALS AND METHODS: This is a qualitative study with content analysis approach conducted through semi-structured interviews in Isfahan University of Medical Sciences from April to December 2017. A total of 35 participants (11 patients, 9 nurses, 6 faculty members, 4 postgraduate students, and 5 nursing managers) were included in the study. Sampling was done based on purposive sampling method, and participants were asked to express their opinions about nurse consultant. RESULTS: In this article, we discussed the following three categories and seven subcategories: (1) nursing consultation as a treatment facilitator (nursing consultation as a way to reduce the treatment course, nursing consultation as a way to reduce complications, and nursing consultation as a way to reduce costs); (2) professional performance in nursing consultation (nursing consultation based on problem-solving and evidence-based practice and management and teamwork in nursing consultation); and (3) prerequisites for the nursing consultation role (supporting nurses and introducing the role in decision-making units and creating demand). CONCLUSION: Nursing consultation has an essential role in patient health promotion. Therefore, it is better that nurses and other health-care team should be familiar with this vital role.